Formation mechanism of contributors’ self-identity based on social identity in online knowledge communities - Gu, Tongfei; Cheng, Zhichao; Zhang, Zeqian; Li, Cui; Ni, Yuan; Wang, Xiaokang (Frontiers in Psychology, 2022)
Contributors' self-identity is a critical element in the sustainable development of online knowledge communities (OKCs). However, research concerning the formation mechanism of contributors' self-identity remains scarce. This research posits information support, novel posting and sense of self-worth as mediating variables between social identity and self-identity to construct a path model, aiming to explore the way in which self-identity is formed on the basis of social identity in OKCs. To examine this mode, an online survey was administered to many different OKCs, and 515 usable questionnaire responses were collected. Structural equation modeling was then employed to examine the model. We find that self-identity emerges through the mediating effects of information support, novel posting and sense of self-worth. In addition, social identity can elicit novel posting and information support, which are all beneficial for enhancing the dynamics of OKCs and further generate sense of self-worth. We also observe that although social identity and individualized behavior (novel posting) are generally incompatible, they can be compatible in the context of OKCs. Our findings can provide operators of OKCs with theoretical and practical insights into achieving sustainable operation.